Carcinoma In Disguise-Atypical Presentation of Squamous Cell Carcinoma - Kawari Sowbhagyalaxmi Ramesh; Abhishek Ganguly; Abhijith Acharya; Manohar V Pai (Gazi Medical Journal)
Squamous cell carcinoma (SCC) of the nail unit is a rare malignant subungual tumor. There is often a delay in diagnosis and treatment as it can be often misdiagnosed as chronic paronychia, onychomycosis, pyogenic granuloma, subungual wart, or glomus tumor. Here, we present a case of an elderly man who was brought to the out-patient department with a deformed appearance of the right fourth finger of his hand after 1 year. With a preceding history of trauma and two sessions of excision of the finger nail showing onychomycosis, the patient was admitted for further evaluation. Imaging in form of X-ray of the hand and Magnetic resonance imaging of the finger showed bony destruction of middle and distal phalanges, thereby favoring fungal osteomyelitis. However, incisional biopsy from the nail unit revealed suspicious of SCC. A multimodal approach to the tumor is required; however, surgical excision is the definitive treatment.